The effect of moisture on the properties of cement-bonded particleboards made with non-traditional raw materials - Melichar, Tomáš; Mészárosová, Lenka; Bydžovský, Jiří; Lédl, Matěj; Vasas, Silvestr (Springer, 2021)
The paper presents research into the changes of properties in cement-bonded particleboards caused by moisture saturation over the course of 504 h. Three particleboard variants were tested, all at the age of 18 months. The first is a standard production-line board manufactured by CIDEM Hranice, a.s. (identified as CP-R). The other two variants were modified by by-products of the particleboard manufacturing process—dust (CP-D) and a particulate mixture (CP-P). The experiment observed changes in the boards’ dimensions, volume, and mass. The effect of moisture on their basic material properties was also investigated. While the boards were being saturated by water, changes in their structure were examined using an optical microscope. It was found that the boards behave differently depending on their composition. Also there were differences in the dynamics of the property changes. The modified particleboards are more susceptible to dimensional and volume changes. Both, volume and mass undergo the most significant changes during the first 24 h. Cracks and air voids inside the wood chips begin to close upon contact with water as a result of swelling. It was observed by optical microscopy that this process occurs within 3 to 5 min since immersion in the water bath. Between 24 and 96 h the rate at which the air voids and pores are closing begins to decrease and there is a difference in the dynamics of mass and volume changes as well. Wet–dry cycling of the boards was analysed as well. Temperature and moisture fluctuations negatively affected particleboard behaviour and properties. Strength dropped up to 50%. Wider cracks in structure of the particleboards were detected by optical microscopy, namely in ITZ (internal transition zone) of cement matrix and spruce chips.

The paper presents research into the changes of properties in cement-bonded particleboards caused by moisture saturation over the course of 504 h. Three particleboard variants were tested, all at the age of 18 months. The first is a standard production-line board manufactured by CIDEM Hranice, a.s. (identified as CP-R). The other two variants were modified by by-products of the particleboard manufacturing process—dust (CP-D) and a particulate mixture (CP-P). The experiment observed changes in the boards’ dimensions, volume, and mass. The effect of moisture on their basic material properties was also investigated. While the boards were being saturated by water, changes in their structure were examined using an optical microscope. It was found that the boards behave differently depending on their composition. Also there were differences in the dynamics of the property changes. The modified particleboards are more susceptible to dimensional and volume changes. Both, volume and mass undergo the most significant changes during the first 24 h. Cracks and air voids inside the wood chips begin to close upon contact with water as a result of swelling. It was observed by optical microscopy that this process occurs within 3 to 5 min since immersion in the water bath. Between 24 and 96 h the rate at which the air voids and pores are closing begins to decrease and there is a difference in the dynamics of mass and volume changes as well. Wet–dry cycling of the boards was analysed as well. Temperature and moisture fluctuations negatively affected particleboard behaviour and properties. Strength dropped up to 50%. Wider cracks in structure of the particleboards were detected by optical microscopy, namely in ITZ (internal transition zone) of cement matrix and spruce chips.
The effect of moisture on the properties of cement-bonded particleboards made with non-traditional raw materials
Keywords: Cement-bonded particleboard; Modification; Composition; Water saturation; Wet–dry cycle; Dynamics; Volume; Mass; Strength; Sugar content; Microstructure; Cement-bonded particleboard; Modification; Composition; Water saturation; Wet–dry cycle; Dynamics; Volume; Mass; Strength; Sugar content; Microstructure